Analysis of Intercarrier Interference Cancellation Scheme in OFDM Systems - Nasir Salh Almisbah; Elessaid S Saad (Computer Engineering and Applications Journal (ComEngApp), 2012)
Abstract: Orthogonal Frequency Division Multiplexing (OFDM) is an emerging multi-carrier modulation scheme, which has been adopted for several wireless standards such as IEEE 802.11a and HiperLAN2. In OFDM systems, the performance is very sensitive to subcarrier frequency errors (offset). This paper shows the analysis and derivations of intercarrier interference (ICI) complex gain that used in self-cancellation scheme and its dependence on subcarrier frequency offset. Simulation shows that better improvement in performance is achieved for systems that use this cancellation scheme. Moreover, analysis and simulation show that theoretical carrier-to-interference ratio (CIR) for OFDM with cancellation scheme is greater than conventional one by more than 14dB.